Business ethics and continental philosophy - Painter-Morland, Mollie Ed; Bos, René ten Ed (Cambridge University Press, 2011)
"Business ethics has largely been written from the perspective of analytical philosophy with very little attention paid to the work of continental philosophers. Yet although very few of these philosophers directly discuss business ethics, it is clear that their ideas have interesting applications in this field. This innovative textbook shows how the work of continental philosophers - Deleuze and Guattari, Foucault, Levinas, Bauman, Derrida, Levinas, Nietzsche, Zizek, Jonas, Sartre, Heidegger, Latour, Nancy and Sloterdijk - can provide fresh insights into a number of different issues in business ethics. Topics covered include agency, stakeholder theory, organizational culture, organizational justice, moral decision-making, leadership, whistle-blowing, corporate social responsibility, globalization and sustainability. The book includes a number of features designed to aid comprehension, including a detailed glossary of key terms, text boxes explaining key concepts, and a wide range of examples from the world of business"--